ADAPTIVE REUSE AS AN APPROACH TO PRESERVE HERITAGE BUILDINGS - Tandy, Nicholas; Sembiring, Sri Gunana (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Indonesia, with its long and diverse history, is home to a wealth of heritage buildings that reflect its rich cultural and architectural legacy. By applying adaptive reuse on these heritage buildings, which is a sustainable approach that repurposes old structures for modern uses while preserving their historical and cultural significance. This method not only conserves architectural heritage but also promotes economic, environmental, and also social benefits. In Indonesia, where many heritage buildings are at risk due to urbanization and neglect, adaptive reuse offers a solution to maintain these structures. The importance of adaptive reuse lies in its ability to integrate historical value with contemporary needs, thus enriching the cultural landscape and fostering community identity. The impact of adaptive reuse in Indonesia can be significant, leading to the revitalization of urban areas, the promotion of tourism, and the creation of economic opportunities. Moreover, it addresses the issues of land scarcity and environmental degradation by reducing the need for new construction. By embracing the approach of adaptive reuse, Indonesia can ensure its rich architectural heritage continues to thrive in a modern context, offering future generations a tangible connection to the past while meeting the contemporary needs.